Effect of the Culture Medium of the Pathogenic Entomo Fungus Metarhizium sp on the Growth Rate and Pathogenicity in Larvae of Oryctesrhinoceros in the Laboratory - Sulaiman Ginting; S. Edy Sumantri; Dendi Putra Siregar (Jurnal Penelitian Pendidikan IPA, 2025)
Oryctes rhinoceros is a major pest in oil palm plantations, causing serious yield losses. Biological control using the entomopathogenic fungus Metarhizium sp. is a safer alternative to chemical insecticides. This study aimed to evaluate the effect of different culture media on the growth and pathogenicity of Metarhizium sp. against O. rhinoceros larvae. The experiment used a Completely Randomized Design with seven treatments: sterile aquadest (control), PDA, PDA + O. rhinoceros extract, corn medium, corn medium + O. rhinoceros extract, rice medium, and rice medium + O. rhinoceros extract. Observed parameters were colony diameter, initial time of larval mortality, and larval mortality. The results showed that culture medium significantly affected colony growth and virulence of Metarhizium sp. Corn medium supplemented with O. rhinoceros extract (A4) produced the largest colony diameter (95 mm at 23 days after inoculation) and the fastest onset of mortality (8.33 days). All Metarhizium sp. treatments caused high mortality of O. rhinoceros larvae under laboratory conditions. These findings indicate that nutrient-rich media, particularly corn combined with insect extract, enhance the performance of Metarhizium sp. and support its use as an effective biological control agent against O. rhinoceros